Risk early warning and control of food safety based on an improved analytic hierarchy process integrating quality control analysis method. (February 2020) - Ma, Bo; Han, Yongming; Cui, Shiying; Geng, Zhiqiang; Li, Hongda; Chu, Chong
Abstract: Food safety risks has received great attention in all world. And the reasonable effectiveness of security warnings can reduce public panic and risk losses. Therefore, this paper proposes an improved risk early warning method for food safety detection data based on the analytic hierarchy process (AHP) integrating the quality control analysis method. The AHP based on the entropy weight can obtain risk values for food safety component data. And the risk matrix of the risk component is obtained by the risk probabilities of the components. Then the corresponding risk levels are calculated using the quality control analysis method to release the risk warning information. Finally, a case study of dairy product safety data from the GuiZhou province in China is conducted to verify the feasibility and reliability of the proposed method. Moreover, the proposed method can scientifically and reasonably determine the risk level information. Furthermore, the risk management is provided to effectively reduce risk losses of the country though relevant quality inspection departments. Highlights: An improved AHP integrating quality control analysis method is proposed. The validity and the practicability of the proposed method are verified by dairy product safety data. The risk early warning and control results of food safety can be obtained. The proposed method can guide relevant departments to formulate or adjust the risk control measures.